East Asian Growth Before and After the Crisis - Crafts, N. (IMF Working Papers; Working Paper ;, 1998)
This paper surveys the literature on the growth performance of the east Asian economies in recent decades, evaluates the sustainability of that performance, and provides a preliminary assessment of their long-term growth prospects in the aftermath of the current crisis. It highlights three special aspects of east Asian growth: unusually high factor accumulation, a favorable demographic transition, and the impact of rapid growth on financial and other institutions. The paper argues that there are downside risks to the east Asian 'developmental state' model, despite its favorable attributes, and that an alternative model may become more attractive as these economies mature.